STRATEGI GURU DALAM MEMANIFESTASIKAN KEBIASAAN DISIPLIN KEPADA PESERTA DIDIK DI PITTAYAPHAT SUKSA SCHOOL THAILAND - Khairullah Khairullah; Abd Rahman (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to describe the strategies teachers use to instill disciplinary habits in students at Pittayaphat Suksa School, Thailand. The study employed a qualitative approach using a case study design. Data were collected from seven informants selected through purposive sampling, consisting of four subject teachers, two guidance counselors, and one school principal, via semi-structured interviews, non-participant observation, and document analysis. Data analysis was based on the interactive model of Miles and Huberman. The research findings indicate that teachers employ five mutually integrated strategies: modeling as the primary moral foundation; habit formation through structured daily routines; positive reinforcement tailored to students’ characteristics; dialogic educational sanctions; and participatory classroom management. The implementation of disciplinary habits encompasses three dimensions: time discipline, study discipline, and behavioral discipline. Supporting factors include the principal’s leadership commitment, a collaborative culture among teachers, and active parental involvement. Meanwhile, inhibiting factors include inconsistencies in rule enforcement among teachers, the influence of social media and technology on student behavior, and cultural diversity that demands different approaches. This study concludes that the successful internalization of disciplinary values requires a holistic, consistent, and humanistic approach involving all components of the educational ecosystem.